Theoretical and practical aspects of pedagogy and psychology - Emelianova I. E., Mangova O. B., Vlasicheva V. V., Glotova G. A., Fedotov E. D., Liakhova E. G., Glagolev A. B., Dushina I. V., Sidorova L. V., Salankova S. E., Serkova E. I., Mueva A. V., Akhmetzianova E. I., Akhtarieva R. F., Shapirova R. R., Sofronova S. A., Vasileva I. S., Shvaikina N. S., Zaluzhnaia M. V., Krutova I. A., Fisenko M. A., Matveichik T. V., Smyslova G. A., Usheva T. F., Kozhevnikova V. V., Soboleva T. N., Kazakova T. A., Pozdnyakov A. N., Burukina O. A. (Theoretical and practical aspects of pedagogy and psychology, 2023)
the Year of Peace and Creation declared by the President of the Republic of Belarus Lukashenko A.G. Decree No. 1 of January 1, 2023, gave greater incentive and specificity in the design of public health promotion measures youth in the republican action plan. The health of pupils and students is in the area of interest socially oriented state, as evidenced by the systemic work and achievements in the field of solving the problems of demographic security, versatile international cooperation of the Ministry Health care Republic Belarus, opinions conferences at the level of Ministers of Health in Vienna (1988) and Munich (2000) [21, p. 15–20; 35, p. 175–178]. A holistic approach to the creation in schools of the Republic of Belarus healthy learning environment is a strategy used to effective school health since 2000. FRESH initiative (Focusing Resources on Effective School Health «Forming Resources for Effective School Health») has been identified in partnership with UNESCO, UNICEF, WHO and the World bank. Essential Components for a Child-Friendly School («Child Friendly Schools») or «Health Promoting Schools students» («Health Promoting School») focused on interventions that could be effectively implemented even in the least resourced schools [5, p.25].
Keywords: школа; медицинская сестра; nurse; профилактическая помощь; содействующая укреплению здоровья; preventive care; health promoting school